1999
DOI: 10.1097/00001756-199912160-00007
|View full text |Cite
|
Sign up to set email alerts
|

Non-conscious recognition of affect in the absence of striate cortex

Abstract: Functional neuroimaging experiments have shown that recognition of emotional expressions does not depend on awareness of visual stimuli and that unseen fear stimuli can activate the amygdala via a colliculopulvinar pathway. Perception of emotional expressions in the absence of awareness in normal subjects has some similarities with the unconscious recognition of visual stimuli which is well documented in patients with striate cortex lesions (blindsight). Presumably in these patients residual vision engages alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
227
3
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(247 citation statements)
references
References 16 publications
16
227
3
1
Order By: Relevance
“…As in the original study, the patients, prompted by consciously perceived auditory stimuli, are forced to guess and to press different buttons for different emotions that may be displayed (de Gelder et al, 1999;Pegna et al, 2005;Van den Stock et al, 2011). Most commonly, direct behavioral measures rely on response accuracy and latency.…”
Section: Methodological Issues In the Study Of Affective Blindsightmentioning
confidence: 99%
See 2 more Smart Citations
“…As in the original study, the patients, prompted by consciously perceived auditory stimuli, are forced to guess and to press different buttons for different emotions that may be displayed (de Gelder et al, 1999;Pegna et al, 2005;Van den Stock et al, 2011). Most commonly, direct behavioral measures rely on response accuracy and latency.…”
Section: Methodological Issues In the Study Of Affective Blindsightmentioning
confidence: 99%
“…Thus, it has been proposed, and later on verified with different neuroimaging methods, that considerable post-lesion and experience-dependent plasticity has taken place in GY's brain (Bridge et al, 2008;Tamietto et al, 2012). Although we will discuss the neural underpinnings of affective blindsight in a dedicated section below, it has become increasingly clear that affective blindsight is not such a rare phenomenon, for it has been reported in more than 20 different patients studied by at least five independent research teams in several different countries (Anders et al, 2004(Anders et al, , 2009Bertini et al, 2013;Cecere et al, 2014;de Gelder & Hadjikhani, 2006;de Gelder et al, 1999de Gelder et al, , 2002de Gelder et al, , 2005de Gelder et al, , 2014Hamm et al, 2003;Heywood & Kentridge, 2000;Morris et al, 2001;Pegna et al, 2005;Rossion et al, 2000;Tamietto & de Gelder, 2008;Tamietto et al, 2009Tamietto et al, , 2012Van den Stock et al, 2011). These patients suffered different lesions to the visual cortex at different ages, but for the large majority in adulthood, and two of them had bilateral cortical blindness.…”
Section: What Could Be Mistaken About Affective Blindsight?mentioning
confidence: 99%
See 1 more Smart Citation
“…New experiments on affective blindsight investigated possible online interaction between the aware and the unaware modes of emotional processing, as well as the influence exerted by unseen emotions over ongoing recognition of other consciously perceived stimuli(de Gelder, Morris, & Dolan, 2005;de Gelder, Pourtois, van Raamsdonk, Vroomen, & Weiskrantz, 2001;de Gelder, Pourtois, & Weiskrantz, 2002;Tamietto, Weiskrantz, Geminiani, & de Gelder, 2007). This series of studies took advantage of indirect methods of testing which, as compared to direct "guessing" methods, cannot be influenced by deliberate response strategies used by the patient.…”
Section: Nonconscious or Unattended Perceptionmentioning
confidence: 99%
“…In an initial study, de Gelder et al (1999) showed that a patient was able to guess above chance level the expression of emotional faces, even though he was unaware of the presence of the stimulus. Another study on a patient (TN) with bilateral V1 destruction (Pegna et al, 2005) showed that emotionally expressive faces elicited brain responses, notably in the right amygdala.…”
Section: Introductionmentioning
confidence: 99%